Critical role of non-coding RNA-mediated ferroptosis in urologic malignancies - Li, Wei; Zheng, Liying; Luo, Peiyue; Chen, Tao; Zou, Jun; Chen, Qi; Cheng, Le; Gan, Lifeng; Zhang, Fangtao; Qian, Biao (Frontiers in Immunology, 2024)
Urologic malignancies, characterized by their high aggressiveness and metastatic potential, pose a significant public health challenge globally. Ferroptosis, a novel mode of cell death, typically arises from intracellular iron ion overload and the accumulation of lipid peroxides. This process has been shown to play a crucial regulatory role in various pathological conditions, particularly in cancer, including urologic cancers.However, the comprehensive regulatory mechanisms underlying ferroptosis remain poorly understood, which somewhat limits its broader application in cancer therapy. Non-coding RNAs (ncRNAs), which encompass microRNAs (miRNAs), long noncoding RNAs (lncRNAs), and circular RNAs (circRNAs), are non-coding transcripts that play pivotal roles in various physiological processes, such as proliferation, differentiation, apoptosis, and cell cycle regulation, by modulating the expression of target genes. The biological functions and potential regulatory mechanisms of ncRNAs in the context of cancer-related ferroptosis have been partially elucidated. Research indicates that ncRNAs can influence the progression of urologic cancers by affecting cell proliferation, migration, and drug resistance through the regulation of ferroptosis.Consequently, this review aims to clarify the functions and mechanisms of the ncRNAferroptosis axis in urologic cancers and to evaluate the clinical significance of ferroptosis-related ncRNAs, thereby providing new insights into cancer biology and therapeutic strategies that may ultimately benefit a diverse range of cancer patients.